Knowledge and Attitude in Hamadan University of Medical Sciences Students toward AIDS: A Cross- Sectional Study from West of Iran - Yazdi-ravandi, Saeid; Taslimi, Zahra; Ghaleiha, Ali; Azhdarloo, Mohammad; Shamsaei, Farshid (International Clinical Neuroscience Journal, 2017)
Introduction: Young people are the major group at risk of acquiring AIDS worldwide. It is one of the health problems in the world, in particular in developing countries. In this study, knowledge and attitude of Iranian students in Hamadan University of Medical Sciences toward HIV and AIDS was assessed. Methods: This investigation was a descriptive cross-sectional study. 509 students were selected from Hamadan University of Medical Sciences schools by sampling methods in 2014-2015. To collect data, the demographic and the international AIDS questionnaire was used. Data analysis was performed by the Mann-Whitney and Kruskal-Wallis test with SPSS-16 software. Results: It was found that the means and standard deviation of knowledge score and attitude towards AIDS in general were 53.86±6 and 20.21±3.29, respectively. The results showed that no significant difference was seen between gender and level of knowledge (P=0.391) and attitude about AIDS (P=0.104). The results of the Kruskal-Wallis test showed a significant difference between faculty and students knowledge (P=0.012). Also, the findings illustrated that there was no significant relationship between faculty (P=0.147) and level of education (P=0.289) and their attitude to AIDS sufferers. Conclusion: The overall rate of knowledge and attitude about HIV/AIDS among students in Hamadan University of Medical sciences was acceptable and good. It is proposed that information about AIDS/HIV issues as part of the course content plan for all students. Young people are most at risk of HIV, proper training is essential to raise young people knowledge.